2019
DOI: 10.3390/w12010035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deforestation on Water Flow in the Vadose Zone

Abstract: The effects of land use change on the occurrence and frequency of preferential flow (fast water flow through a small fraction of the pore space) and piston flow (slower water flow through a large fraction of the pore space) are still not fully understood. In this study, we used a five year high resolution soil moisture monitoring dataset in combination with a response time analysis to identify factors that control preferential and piston flow before and after partial deforestation in a small headwater catchmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…In this context, Lange et al (2009) [65] were able to demonstrate positive effects of tree root density on rapid infiltration in stagnic soils. Wiekenkamp et al (2019) [66] compared in the Wüstebach (BRD) catchment the hydrology of a forest site with the neighboring clear-cut site. They concluded that infiltration via preferential flow paths increased after deforestation.…”
Section: Ecohydrologymentioning
confidence: 99%
“…In this context, Lange et al (2009) [65] were able to demonstrate positive effects of tree root density on rapid infiltration in stagnic soils. Wiekenkamp et al (2019) [66] compared in the Wüstebach (BRD) catchment the hydrology of a forest site with the neighboring clear-cut site. They concluded that infiltration via preferential flow paths increased after deforestation.…”
Section: Ecohydrologymentioning
confidence: 99%
“…Regional simulations could thus benefit from regional soil maps, where available. In addition, land cover changes can affect soil properties (Wiekenkamp et al, 2020), which means that the adjustment of SHPs in response to vegetation changes (such as deforestation) could further improve LSM simulations.…”
Section: Shortcomings and Scope For Further Researchmentioning
confidence: 99%
“…They found that the lower evapotranspiration caused an increase in soil water content in the deforested portion of the catchment in the first 2 years after deforestation, especially during the summer periods, which led to a greater number of high flows. In addition, Wiekenkamp et al (2020) found that the partial clear-cut increased the occurrence of preferential flow in the deforested area.…”
Section: Introductionmentioning
confidence: 98%
“…From August to September 2013, 8.6 ha of the catchment area of the Wüstebach were cleared to allow natural succession to a mixed beech (Fagus sylvatica) forest (Figure 1). This deforestation has impacted the hydrological system of the Wüstebach catchment in many ways (Wiekenkamp et al, 2020;Wiekenkamp et al, 2016a). Evapotranspiration in the clear-cut area was first reduced by approximately 50% and returned towards pre-cut values during the first 2 years (Ney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%